COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) MODEL LEARNING PLAN IN IMPROVING ENGLISH READING SKILL - Rifqi Zaeni Achmad Syam; Rosiana Nurwa Indah; R. Supyan Sauri; Farah Ruqayah (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2020)
Abstract:This study aimed to obtain an overview of the Cooperative Integrated Reading and Composition learning planning model to improve grade IX students' English reading skills at SMP Negeri 1 Jampang Tengah. The method used in this study was a descriptive method with a qualitative approach, and the research subjects were English teachers at SMP Negeri 1 Jampang Tengah. The data collection was done through document review, observation, and interviews. From the study results, it could be concluded that the Cooperative Integrated Reading and Composition Model's learning planning activities consisted of making annual programs, semester programs, syllabus, and lesson plans. In principle, it was good and appropriate to make lesson plans with the school's provisions and guidelines. Therefore, it was believed to achieve the specified competency standards and improve reading skills in English.Abstrak:Penelitian ini bertujuan untuk memperoleh gambaran tentang perencanaan pembelajaran model Cooperative Integrated Reading and Composition dalam meningkatkan keterampilan membaca bahasa Inggris siswa kelas IX di SMP Negeri 1 Jampang Tengah. Metode dalam penelitian ini menggunakan metode deskriptif dengan pendekatan kualitatif. Subjek penelitian ini adalah guru bahasa Inggris di SMP Negeri 1 Jampang Tengah. Adapun Pengumpulan data dilakukankan melalui pengkajian dokumen, observasi dan wawancara. Dari hasil penelitian, dapat disimpulkan bahwa kegiatan perencanaan pembelajaran model Cooperative Integrated Reading and Composition terdiri dari pembuatan program tahunan, program semester, silabus dan RPP. Pada prinsipnya sudah baik dan sesuai dalam pembuatan perencanaan pembelajaran dengan ketentuan dan pedoman yang di tetapkan oleh pihak sekolah. Oleh karenanya, diyakini dapat mencapai standar kompetensi yang ditentukan dan dapat meningkatkan keterampilan membaca bahasa Inggris.